Work of adhesion between mucin macromolecule and calcium-alginate gels on molecular level. (5th June 2015) - Popeski-Dimovski, Riste
Highlights: AFM is used to follow the bioadhsion between mucin macromolecule and alginate gel layer. Work of adhesion is evaluated from G/M ratio and crosslink ratio of the alginate gel. A Gompertz growth distribution is determined for the time dependent increase of the work of bioadhesion. Abstract: The bioadhesion of biopolymers to mucus layers is of great interest for the development of drug delivery systems. Herein we use AFM force measurements to evaluate the interaction on molecular level between a mucin macromolecule attached to an AFM tip and a calcium-alginate gel layer. The total work of adhesion is measured from the AFM force curves depending on different parameters: time of contact, G/M ratio of the alginate, and crosslink ratio of the gel. The total work of adhesion is found to be in the range of 1 × 10 −19 to 6 × 10 −18  J. The results show that the work of adhesion increases with the time of contact but it is independent from the molecular mass of the alginate, the G/M ratio of the alginate and crosslink ratio of the gel.